Huangqi Shengmai Yin Ameliorates Myocardial Fibrosis by Activating Sirtuin3 and Inhibiting TGF-β/Smad Pathway - Pan, Jianheng; Cao, Zhanhong; Fang, Chunqiu; Lei, Yuting; Sun, Jiaming; Huang, Xiaowei; Han, Dong (Frontiers in Pharmacology, 2021)
Abstract Myocardial fibrosis (MF) is an important pathological process in which a variety of cardiovascular diseases transform into heart failure. The main manifestation of MF is the excessive deposition of collagen in the myocardium. Here, we explored whether Huangqi Shengmai Yin (HSY) can inhibit isoprenaline (ISO)-induced myocardial collagen deposition in rats, thereby reducing the cardiac dysfunction caused by MF. The results of echocardiography showed that HSY upregulated fractional shortening and ejection fraction, and reduced the left ventricular systolic dysfunction in the rats with MF. Pathological results showed that HSY protected myocardium, inhibited apoptosis, and effectively reduced collagen deposition. HSY also inhibited the expression of collagen I and III and α-smooth muscle actin (α-SMA) in the heart tissue. HSY increased the expression of Sirtuin 3 (Sirt3) and inhibited the protein levels of the components in the transforming growth factor-β (TGF-β)/Smad pathway. At the same time, it also regulated the expression of related proteins in the matrix metalloproteinases family. In summary, HSY played a therapeutic role in rats with ISO-induced MF by protecting myocardium and inhibiting collagen deposition. Therefore, HSY is a potential therapeutic agent for ameliorating MF.